Writing politics : studies in compositional method - Shapiro, Michael J. (New York : Routledge, 2021)
"Writing Politics is a methods book designed to instruct on politically focused literary inquiry. Exploring the political sensibilities that arise from the way literary fiction re-textualizes historical periods and events, the book features a series of violence-themed inquiries that emphasize forms of writing as the vehicles for politically attuned historiography. Each investigation treats the way the literary genre, within historiographic metafiction, enables political inquiry. It's a form of writing that inter-articulates history and fiction to rework a textual past and unsettle dominant understandings of events and situations. Central to the diverse chapter are fictional treatments of authoritarian, fascist, or zealous mentalities. Featured, for example, are Radovan Karadzic (the architect of the Bosnian genocide), Reinhard Heydrich (the architect of the Holocaust's "final solution"), and the Trotsky assassin Ramon Mercader. Michael J. Shapiro has produced another original and sophisticated bookshelf staple; the only contemporary investigation in Political Studies that instructs on method in this way"--
Keywords: Political science -- Authorship; Scripting mentality